INTRODUCTION OF HANDS-ON PROJECTS INVOLVING 8 INTELLIGENCES AND 21 WORK-READINESS SKILLS TO BOOST MOTIVATION IN ENGLISH PRESENTATION COURSES - Nga, Nguyen Thi Hang (VNU Journal of Foreign Studies; Vol 36 No 5DO - 10.25073/2525-2445/vnufs.4616, 2020)
Teaching-learning innovation has always been one of the national and educational leaders’ political goals. “True learning, true career" has been known as a tough goal in Vietnam’s latest national policy in education. Our research means to incorporate highly practical and hands-on projects involving 21 work-readiness skills and 8 intelligences to boost motivation in English presentation courses. Core concepts from Vietnamese Party’s latest education reform policies, global education trends and WEF workforce forecast in 2018 have shed light on this 3-year study which then engaged 05 classes of English non-majored Advanced Program students in Vietnam National University. The data were exploited through online questionnaires, print questionnaires, indepth interviews and teaching logs. The results show an encouraging progress in all target skills among which creative skills, listening skills, language skills dominated, thereby increasing learners inspiration. The teachers also get more proactive and sense more opportunities for innovation. Hopefully, the article may be a friendly and easy implication for practitioners still confused when applying new concepts, contribute to innovative tertiary education and proudly and delightedly share the achievements of our hands-on courses.